2015
DOI: 10.1089/jayao.2014.0048
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Fertility Preservation for Lesbian, Gay, and Bisexual Adolescents and Young Adults with Cancer

Abstract: A dolescents and young adults (AYAs) with cancer are informed of their risk of sub-fertility and options for fertility preservation (FP) with the intention that, if possible, they are able to consider having biologically related children after treatment. Previous research indicates that assumptions of heterosexuality are a prevalent experience in healthcare among lesbian, gay, bisexual, and transgender (LGBT) populations. 1,2 Accordingly, pervasive heterosexual bias among providers may frame conversations on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…While there are numerous narrative reviews on the topic, there has not yet been a systematic assessment of the research base (18)(19)(20). The purpose of this systematic review is to characterize patient and provider perspectives on LGBTQþ cultural competence and fertility care.…”
mentioning
confidence: 99%
“…While there are numerous narrative reviews on the topic, there has not yet been a systematic assessment of the research base (18)(19)(20). The purpose of this systematic review is to characterize patient and provider perspectives on LGBTQþ cultural competence and fertility care.…”
mentioning
confidence: 99%
“…4 Some studies have reported that SGM and young adult patients with cancer are less likely to be counseled on potential infertility or offered fertility preservation consults. 5…”
Section: To the Editormentioning
confidence: 99%
“…4 Some studies have reported that SGM and young adult patients with cancer are less likely to be counseled on potential infertility or offered fertility preservation consults. 5 In view of strong evidence of health disparities in oncology for the SGM community, [6][7][8] hematology and oncology fellow education related to sexual and reproductive health provides a useful opportunity for continuing education about culturally appropriate health care for SGM oncology patients. Cathcart-Rake et al 2 provided a mini curriculum with the goal of helping cancer health care providers to ask patients with cancer about SGM status and to ask all patients with cancer about sexual health issues.…”
mentioning
confidence: 99%
“…The online survey included a combination of validated and unvalidated measures, closed-ended questions and open-ended prompts, described in detail elsewhere [14]. The ten-item Kessler Psychological Distress Scale (K10) [34] asked participants to rate the frequency of distressing feelings over the past four weeks, to produce a total distress score (range 10-50), which can then be categorized as low (10)(11)(12)(13)(14)(15), moderate (16-21), high (22)(23)(24)(25)(26)(27)(28)(29) or very high distress [35]. The remaining items used in this analysis were derived from existing LGBTQ surveys, presented in Likert scales, and included: items on minority stress, asked using separate wording for LGBQ, trans and gender diverse (TGD) and intersex participants -discomfort being LGBTQI and control over disclosure [36][37][38], discrimination in general life and in cancer care [2], outness in general life and to HCPs [39]; physical concerns relating to cancer and treatment impacts on the body (e.g.…”
Section: Survey and Measuresmentioning
confidence: 99%